Fostering Sustainable Biomedical Research Training in Mozambique: A Spin-Off of the Medical Education Partnership Initiative - Emília Virgínia Noormahomed; Sérgio Noormahomed; Delfina Hlashwayo; Emília Martins; Mamudo Ismail; Stephen W. Bickler; Jean Nachega; Manuel Mahoche; Kim E. Barrett; Constance A. Benson; Robert T. Schooley (Annals of Global Health, 2022)
Background: The further development of research capacity in low- and middle-income countries is critical to the delivery of evidence-based healthcare, the design of sound health policy and effective resource allocation. Research capacity is also critical for the retention of highly skilled faculty and staff and for institutional internationalization. Objectives: We summarize the accomplishments, challenges and legacy of a five-year program to train biomedical researchers entitled “Enhanced Advanced Biomedical Research Training for Mozambique (EABRTM)”. Methods: A program conducted from 2015–2021 built upon the Medical Education Partnership Initiative to develop research capacity at Eduardo Mondlane University (UEM) and allied institutions. The project included design and implementation of postgraduate training programs and bolstered physical and human research infrastructure. Findings: The program supported development and implementation of UEM’s first doctoral (Bioscience and Public Health) and master (Biosciences) programs with 31 and 23 students enrolled to date, respectively. Three master programs were established at Lúrio University from which 176/202 (87.1%) and 107/202 (53.0%) students obtained a Postgraduate Diploma or master’s degree, respectively. Scholarships were awarded to 39 biomedical researchers; 13 completed master degrees, one completed a PhD and five remain in doctoral studies. Thirteen administrative staff and four biomedical researchers were trained in research administration and in biostatistics, respectively. A total of 119 courses and seminars benefited 2,142 participants. Thirty-five manuscripts have been published to date in peer-reviewed international journals of which 77% are first-authored by Mozambicans and 44% last-authored by Africans. Sustainability was achieved through 59 research projects awarded by international agencies, totaling $16,363,656.42 and funds ($ 7,319,366.11) secured through 2025. Conclusions: The EABRTM program substantially increased research and mentorship capacity and trained a new generation of biostatisticians and research administrators. These programmatic outcomes significantly increased the confidence of early stage Mozambican researchers in their ability to successfully pursue their career goals.